2022
DOI: 10.1073/pnas.2107224119
|View full text |Cite
|
Sign up to set email alerts
|

Modeling suggests gene editing combined with vaccination could eliminate a persistent disease in livestock

Abstract: Recent breakthroughs in gene-editing technologies that can render individual animals fully resistant to infections may offer unprecedented opportunities for controlling future epidemics in farm animals. Yet, their potential for reducing disease spread is poorly understood as the necessary theoretical framework for estimating epidemiological effects arising from gene-editing applications is currently lacking. Here, we develop semistochastic modeling approaches to investigate how the adoption of gene editing may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…A recent modelling study revealed that gene editing, when effectively combined with other disease control strategies, such as vaccination, may be able to eliminate persistent livestock diseases that are currently difficult to control. 676 However, according to this study, such desirable outcomes can only be achieved if the distribution of genetically resistant individuals into commercial populations is coordinated by breeding companies or national schemes.…”
Section: Optimising Implementation and Dissemination To Achieve Popul...mentioning
confidence: 96%
“…A recent modelling study revealed that gene editing, when effectively combined with other disease control strategies, such as vaccination, may be able to eliminate persistent livestock diseases that are currently difficult to control. 676 However, according to this study, such desirable outcomes can only be achieved if the distribution of genetically resistant individuals into commercial populations is coordinated by breeding companies or national schemes.…”
Section: Optimising Implementation and Dissemination To Achieve Popul...mentioning
confidence: 96%
“…This achievement has received financial support from Genus plc (PIC, 2021), an international leader in the porcine and bovine genetics industry with worldwide presence. Based in the use of this tool it is possible to eliminate this persistent disease in few years without sacrificing animals (Petersen et al, 2022), a strategy never implemented before in any other eradication program.…”
Section: Animal Healthmentioning
confidence: 99%
“…All strategies described above are also relevant to gene-edited resistance, including the use of other interventions to assist in decreasing the reproduction ratio to a value below 1 [ 68 ]. Resistance to the porcine reproductive and respiratory syndrome virus is a clear example where gene-editing might be an interesting strategy for infection control [ 68 ], although it is questionable whether many more of such cases exist.…”
Section: Implications For Animal Breedingmentioning
confidence: 99%